2011
DOI: 10.1073/pnas.1111966108
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription-6 (STAT6) inhibition suppresses renal cyst growth in polycystic kidney disease

Abstract: Autosomal-dominant (AD) polycystic kidney disease (PKD) is a leading cause of renal failure in the United States, and currently lacks available treatment options to slow disease progression. Mutations in the gene coding for polycystin-1 (PC1) underlie the majority of cases but the function of PC1 has remained poorly understood. We have previously shown that PC1 regulates the transcriptional activity of signal transducer and activator of transcription-6 (STAT6). Here we show that STAT6 is aberrantly activated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 42 publications
7
63
0
1
Order By: Relevance
“…into the SC-We found previously that STAT6 is aberrantly activated in renal cyst-lining epithelial cells in two mouse models of PKD, the Bpk model and the human-orthologous Pkd1 cond/cond :Nestin cre model (12). In addition, significant amounts of the STAT6 activating cytokine IL13 are present in cyst fluid in these models (12).…”
Section: Pigr Is Expressed In Renal Cyst-lining Cells and Processedmentioning
confidence: 99%
See 3 more Smart Citations
“…into the SC-We found previously that STAT6 is aberrantly activated in renal cyst-lining epithelial cells in two mouse models of PKD, the Bpk model and the human-orthologous Pkd1 cond/cond :Nestin cre model (12). In addition, significant amounts of the STAT6 activating cytokine IL13 are present in cyst fluid in these models (12).…”
Section: Pigr Is Expressed In Renal Cyst-lining Cells and Processedmentioning
confidence: 99%
“…Ϫ/Ϫ animals on a BALB/c background were obtained from The Jackson Laboratory (Bar Harbor, ME) and crossed with the WT/bpk animals as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that the STAT3 signaling pathway is regulated by PC1 and serve as a driver of renal epithelial proliferation during normal kidney development and renal cyst growth. Studies have shown that inhibition of STAT6 by leflunomide (LEF) slows cyst growth in ADPKD mouse models [81].…”
Section: Signal Transducer and Activator Of Transcription (Stats)mentioning
confidence: 99%